Sư̄sān-singwǣtlō̜m - Kānčhanā Kǣothēp; Sīthō̜n Rōtčhanasuphot,$eauthor.; Khrōngkān Mēthī Wičhai ʻĀwusō. Fāi Wichākān (Krung Thēp : Khō̜ngkān Mēthī Wičhai ʻĀwusō, Fāi Wichākān, Samnakngān Kō̜ngthun Sanapsanun Kānwičhai (Sō̜Kō̜Wō̜.), 2013)
Compilation of research on environmental communication.
Includes bibliographical references.
Keywords: Communication in the environmental sciences -- Thailand; Environmental education -- Thailand; Communication -- Social aspects -- Thailand; Mass media and the environment -- Thailand